Mengkonsumsi Makanan Halal Perspektif Al-Qur’an: Telaah Semantik-Historis QS Al-Baqarah ayat 168 - Afrizal El Adzim Syahputra; Nur Faizin; Abduloh Safik; Abul Ma'ali (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Consuming Halal Food from the Perspective of the Qur'an: A Semantic-Historical Study QS. Al-Baqarah verse 168This paper aims to analyze the meaning of halal in QS. Al-Baqarah (2) verse 168 with a semantic-historical approach. The enrichment of the concept of halal food in the Qur'an is important, especially for researchers in the field of Al-Qur'an and commentary. This research is a literature review with a semantic-historical analysis paradigm in QS Al-Baqarah (2): 168. This study found that based on a semantic approach, the word